Объяснение: =3³² -(3⁴-1)(3⁴+1)(3⁸+1)(3¹⁶+1)=3³² - (3⁸-1)(3⁸+1)(3¹⁶+1)=
3³² - (3¹⁶-1)(3¹⁶+1)=3³² - (3³²-1) =3³² -3³²+1= 1.
Объяснение:
3³² - (3² - 1)(3²+ 1)(3⁴ + 1)(3⁸ + 1)(3¹⁶ + 1)=
=3³² - (3⁴ - 1)(3⁴ + 1)(3⁸ + 1)(3¹⁶ + 1)=
=3³² - (3⁸ -1)(3⁸ + 1)(3¹⁶ + 1)=
=3³² - (3¹⁶ -1)(3¹⁶ + 1)=
=3³² - (3³² -1)=
=3³² - 3³² +1=1
Объяснение: =3³² -(3⁴-1)(3⁴+1)(3⁸+1)(3¹⁶+1)=3³² - (3⁸-1)(3⁸+1)(3¹⁶+1)=
3³² - (3¹⁶-1)(3¹⁶+1)=3³² - (3³²-1) =3³² -3³²+1= 1.
Объяснение:
3³² - (3² - 1)(3²+ 1)(3⁴ + 1)(3⁸ + 1)(3¹⁶ + 1)=
=3³² - (3⁴ - 1)(3⁴ + 1)(3⁸ + 1)(3¹⁶ + 1)=
=3³² - (3⁸ -1)(3⁸ + 1)(3¹⁶ + 1)=
=3³² - (3¹⁶ -1)(3¹⁶ + 1)=
=3³² - (3³² -1)=
=3³² - 3³² +1=1